SOME CONVERGENCE RESULTS ON DYNAMIC FACTOR MODELS - CAVICCHIOLI, Maddalena (Theoretical and Practical Research in Economic Fields, 2011)
We review some recent papers on a large dynamic factor model (LDFM) and its applications to structural macroeconomic analysis. Then we prove some convergence results concerning with the stochastic variables which define such a model.